Real-World Patients’ Diagnosis-to-Treatment Journey with Nontuberculous Mycobacterial Pulmonary Disease: A Cross-Sectional Survey - Morimoto, Kozo; Gallagher, Jack R.; Wagner, Dirk; Griffith, David E.; van Ingen, Jakko (Infectious diseases and therapy, 2024)
Introduction The incidence and prevalence of nontuberculous mycobacterial pulmonary disease (NTM-PD) are increasing globally. Approximately 80% of NTM-PD cases in Japan and five countries within Europe (Eur5; France, Germany, Italy, Spain, and the UK) are caused by Mycobacterium avium complex (MAC). This study describes the clinical decision-making process associated with the management of patients with NTM-PD in Japan and the Eur5. Methods We analyzed data from a survey conducted between July 2013 and October 2013 among physicians treating patients with NTM-PD in clinical practice to compare the healthcare settings, clinical presentation, and patient management in Japan and the Eur5. Results Overall, 619 physicians (Japan, 173; Eur5, 446) participated in the survey. Most patients in Japan (85%) and the Eur5 (79%) were diagnosed with MAC-PD. Patients were managed generally in hospital-based outpatient clinics (117/173, 68%) in Japan and research/teaching hospitals affiliated with medical schools (140/446, 31%) in the Eur5. The most common reason for delaying treatment was the patient’s symptoms not being considered serious enough for treatment (55/128, 43%) in Japan and awaiting results of antimicrobial susceptibility testing (44/151, 29%) in the Eur5. Culture negativity was less commonly achieved after treatment in patients in Japan versus those in the Eur5 (31% [73/238] vs. 70% [300/426], p < 0.0001). In treatment phases that were either completed or discontinued, the primary goal was symptomatic improvement, followed by achieving culture conversion, in both Japan and the Eur5. Overall, 19% (16/85) of physicians in Japan and 43% (220/511) in the Eur5 were “entirely satisfied” with their patients’ treatment outcomes. Conclusions Similarities and differences exist in the healthcare settings, clinical presentation, and management of patients with NTM-PD in Japan and the Eur5. Insufficient consideration of culture status by physicians, delayed treatment initiation, and symptom-based cessation emphasize the need for educational efforts on the guideline-based strategies. Plain Language Summary Mycobacteria are microorganisms that cause a disease in the lungs known as nontuberculous mycobacterial pulmonary disease (NTM-PD). The number of people with NTM-PD is increasing globally. This study was a survey of doctors who treated people with NTM-PD in Japan and Europe and aimed to understand geographical similarities and differences in the management, treatment, and health of people with NTM-PD. In the survey, treatment for NTM-PD was found to be often delayed or not started. In Japan, this was most commonly because the individual’s symptoms were not thought to be serious enough and in Europe because of delays in laboratory testing needed to decide which antibiotic treatment should be used. The most common treatment goal in both Japan and Europe was improvement in the individual’s symptoms. Clinical guidelines recommend continuing treatment for at least 12 months after the person with NTM-PD has tested negative for mycobacteria. There were similarities and differences in the healthcare settings, clinical presentation, and management of people with NTM-PD between Japan and Europe. It is important to ensure uniform implementation of the treatment guidelines for NTM-PD in each clinical setting so that people with NTM-PD experience better health outcomes.